2017
DOI: 10.1038/s41598-017-04366-5
|View full text |Cite
|
Sign up to set email alerts
|

Lactate dehydrogenase A promotes the invasion and proliferation of pituitary adenoma

Abstract: Lactate dehydrogenase A (LDHA) has been reported to be involved in the initiation and progression of tumors. However, the potential role of LDHA in pituitary adenoma (PA) remains unknown. In this study, we showed that the expression levels of LDHA mRNA and protein were significantly elevated in invasive PA samples, and positively correlated with higher Ki-67 index. Overexpression of LDHA in a PA cell line (GH3) promoted glucose uptake through the upregulation of glucose transporter-1 (Glut1), lactate secretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 44 publications
2
43
0
1
Order By: Relevance
“…A number of enzymes have been confirmed to be involved in the aerobic glycolysis process, such as GLUT1, LDH-A [15,16]. Furthermore, LDH-A can accelerate cell invasion, proliferation and glucose uptake of pituitary adenoma (PA) cells via upmodulating GLUT1 [17]. Thus, we here determined the GLUT1 and LDH-A expressions following modulation of LINC01391 expression, and found that LINC01391 knockdown accelerated GLUT1 and LDH-A expressions, and meanwhile LINC01391 overexpression restrained GLUT1 and LDH-A expressions ( Figure 5), suggesting that LINC01391 may repress aerobic glycolysis of GC via upmodulating GLUT1 and LDH-A.…”
Section: Discussionmentioning
confidence: 99%
“…A number of enzymes have been confirmed to be involved in the aerobic glycolysis process, such as GLUT1, LDH-A [15,16]. Furthermore, LDH-A can accelerate cell invasion, proliferation and glucose uptake of pituitary adenoma (PA) cells via upmodulating GLUT1 [17]. Thus, we here determined the GLUT1 and LDH-A expressions following modulation of LINC01391 expression, and found that LINC01391 knockdown accelerated GLUT1 and LDH-A expressions, and meanwhile LINC01391 overexpression restrained GLUT1 and LDH-A expressions ( Figure 5), suggesting that LINC01391 may repress aerobic glycolysis of GC via upmodulating GLUT1 and LDH-A.…”
Section: Discussionmentioning
confidence: 99%
“…A number of enzymes are involved in the aerobic glycolysis process, including GLUT1 and LDH-A [19,29]. LDH-A can accelerate the invasion and proliferation of pituitary adenoma through the upmodulation of GLUT1 [30]. Thus, we determined the GLUT1 and LDH-A expressions following overexpression or downmodulation of FAM83H-AS1, and found that knockdown or overexpression of FAM83H-AS1 decreased or increased the expressions of GLUT1 and LDH-A ( Fig.3), as well as the downmodulation or upmodulation of glucose uptake and lactate production levels, indicating that FAM83H-AS1 may affect aerobic glycolysis process of ESCC partly by modulating GLUT1 and LDH-A.…”
Section: Discussionmentioning
confidence: 99%
“…The high levels of lactate may be due to the Warburg effect (11), whereas the low glucose levels may be due to the elevated fructose-6-phosphokinase activity (16), high levels of glucose transporters (17) and increased type II hexokinase activity (18) in gastric cancer tissues. High activity levels of pyruvate kinase and lactate dehydrogenase are associated with cancer proliferation and poor prognosis (19,20), whereas their downregulation in vitro can impair tumor invasion (21,22). Based on these reports, several studies have investigated the influence of normal gravity on physiology and metabolism of cancer (23)(24)(25); however, the effect of gravity metabolism on cells, especially gastric cancer cells, is poorly understood.…”
Section: Effect Of Simulated Microgravity On Metabolism Of Hgc-27 Gasmentioning
confidence: 99%